WOMEN'S POWER AND NATION BUILDING: THE ROLE OF WOMEN AS THE PILLAR OF HINDU CULTURE FROM VEDIC TIMES TO THE PRESENT - Shah, Dhwani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Women have held a high position in Indian culture since the beginning. From Vedic times to the present day, women have made important contributions to society through their divine qualities like beauty, power, knowledge and compassion. This research paper, under the motto of "Nari Mahatmya", reveals the sources of women's power through an in-depth analysis of texts like Vedas, Upanishads, Gita, Ramayana, Mahabharata and Manusmriti. Lakshmi, Saraswati and Kali represent the feminine element as a triple power. Historical women like Gargi, Damayanti, Maitri and modern-day talents like Kalpana Chawla, Lata Mangeshkar, Sudha Murthy and Kiran Bedi show how women can excel in every field. This research paper supports the fact that a complete human being is created only where there is a harmony of feminine and masculine qualities. The symbol of Ardhanarinteswar is a spiritual example of balance. Women are not just collaborators, but also creative, nurturing and transformative forces. The purpose of this research paper is to inspire today's generation to respect the value of women and to recognize their own strength and move forward. From the Vedas and Upanishads to the modern era, women have strengthened various pillars of Indian culture. Women have always created new values in the land of India's great culture. Even today, the contribution of women power in the formation and development of this nation is unparalleled. This research paper has tried to show that India is a nation that has been formed on the basis of women power, is still being formed today and will shine with its luminous presence in the future as well.